New Technologies to Improve the Performance of High Water Cut Wells Equipped With ESP - Al-Obaidi, Sudad H; Khalaf, Fahah H; Smirnov, Vector I (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
The article deals with theoretical and practical issues of improving the efficiency of operation of high-water cut oil wells by developing and applying double-acting pumping systems based on electric submersible pumps. This combination is providing down-hole gravitational separation of oil and produced water, lifting low-water-cut oil to the surface with simultaneous injection of most of the separated water into the absorbing formation without lifting to the surface. Moreover, it is providing low-cost regulation of the ratio of the volumes of the lifted product and the injected water, as well as monitoring the quality of the injected water with the required frequency.